Quality Management Subsystems and their Impact on Business Competitiveness - Ruževičius, Juozas (Ekonomika, 2005)
The paper presents an analysis of the theory and methodology of quality management. A model of quality management subsystems is presented and some of its elements are discussed in relation to its influence on the competitiveness of Lithuanian business. Special attention is given to new aspects of quality assessment, social quality in particular. The fundamental elements of these qualities are also presented. The author conducted surveys of Lithuanian businesses and consumers and has used the obtained data to formulate and test the model and to interpret its elements.